The Outpatient Flow Procedure at the “Ngudi Waluyo” Wlingi Regional General Hospital Uses Canva - Nugraheni, Shevia Dwi; Rusdi, Achmad Jaelani; Suhariyono, Untung Slamet; Ma'roef, Moch. Noer Hoedan (Universitas Ibn Khaldun Bogor, 2025)
Outpatient registration is the initial stage in healthcare services at medical facilities. Ngudi Waluyo Regional General Hospital in Wlingi has demonstrated the ability to meet challenges in implementing outpatient procedures in accordance with established SOPs, while also providing innovations and new information to patients. This study aims to design an outpatient registration flow that is easy for patients to understand, especially in locating the intended polyclinic, particularly for new patients. The flow design was created using the Canva platform with a visual infographic-based approach. The method used is descriptive qualitative, with data collected through field observations and interviews with registration staff. The results of this study show that the use of visual media in the form of clear maps and icons greatly helps patients understand the registration process and directions to the polyclinic. The implementation of this visual design is recommended as a strategy to improve the quality of hospital services.